Makna Keadilan Pada Ketentuan 2:1 (Dua Banding Satu) Dalam Konsep Waris Islam - Sarpika Datumula (Jurnal Litigasi Amsir, 2022)
This research aims to provide valuable information about the understanding and concept of justice that exists in Islamic law where in its discussion focuses on discussing whether the difference in acceptance between male heirs and female heirs has fulfilled the concept of justice in the Islamic inherition system or has different thoughts. The results show that in Islamic law, the essence is that one's faith does not affect the definition, in the sense that everything that is established is just by Allah SWT. Justice is not entirely dependent on human reasoning, for justice itself is always changing from one society to another. Although in the end the diversity of the inheritance division system and the absence of a single legal entity that is a reference for the people in applying the law of inheritance in the community becomes one of the causes of the assumption 2:1 may change in accordance with the law chosen to be applied in terms of the division of inheritance. That this assumption is triggered from the thought that today women do not rule out the possibility of becoming the backbone in the family. Keywords: concept of justice, Islamic inheritance, inheritance section 2:1.